Análise comparativa dos hidrogramas de saída da bacia do Riacho Reginaldo quanto a discretização espacial da chuva - Pontes, Victor Costa (2019)
Precipitation events are random processes in both space and time, but recurrences of extreme events can cause constant damage to the population. To minimize the consequences of heavy rains, hydrological models along with rainfall and remote sensing data are of great importance in understanding the effects and behavior of rainfall in a river basin. Thus, the purpose of this work is to evaluate how a river basin responds to two levels of discretization of rainfall events (concentrated and distributed by sub basin) through the SWMM software from the radar and rainfall data applied to the Reginaldo Creek basin located in the urban area of the city of Maceió-AL. The program is based on hydrological and hydrodynamic models capable of simulating basin responses through parameters collected from it and rainfall time series. The parameters were determined through the literature and parameterization of the model, and the time series were selected through the city's information vehicles, which will report events that had as a consequence flood. The time series were created from the data collection of the rainfall stations and the meteorological radar (for the radar data two different calibrations were applied, the first one was used a coefficient determined in the literature and the second one was used the method of SOAS). Later, the Thiessen polygons method was applied and, finally, the time series that fed the software were generated. The results were generated for two distinct scenarios (concentrated rainfall and distributed by sub basin) and the evaluation parameters were the peak flow, the peak time, the drained volume and the infiltrated volume. From the generated hydrograms the need for calibration of the radar data is clear. The calibrations used approximate the hydrographs generated by the radar data to the hydrographs generated by the rainfall data. All the analyzed events present great variations in the evaluation parameters and the main causes of these divergences are: different CN values for the sub basins and the location of the rainy cores of the events.